The Influence of the Corporate Social Responsibility Implementation on the Company's Image - Rais, Rismawaty; Multazimah, M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study discusses the effect of corporate social responsibility (CSR)implementation on the corporate image in the Simping Mekar Rasa program and aims todetermine the extent of the influence of sustainability, accountability, and transparency on CSRimplementation by the Public Relations of PT Pembangkit Jawa-Bali Cirata Generation Unitthrough the Simping Mekar Rasa program on companies image which includes indicators ofperception, cognition, motivation and attitudes of the assisted group members. This researchuses quantitative methods. In this study, a sample of 22 respondents was taken, using asaturated sampling technique. The results showed that there was a positive and significanteffect of sustainability on the corporate image by 42.5%. There is a positive and significantinfluence between accountability on the corporate image of 43.2%. There is a positive andsignificant influence between transparency on the company image of 38.9%. There is a positiveand significant influence between CSR implementation on perceptions of 65.8%. There is apositive and significant influence between CSR implementation on cognition of 54.5%. Thereis a positive and significant influence between CSR implementation on motivation by 42.1%.There is a positive and significant influence between the implementation of CSR on attitudesof 79.1%. The conclusion of this study can be said that there is a positive and significantinfluence between the implementation of CSR on the corporate image of 54.1%.